1998
DOI: 10.1046/j.1365-2265.1998.00572.x
|View full text |Cite
|
Sign up to set email alerts
|

Osmoregulation in clinical disorders of thirst appreciation

Abstract: The pseudohypoparathyroid disorders appear to represent a heterogeneous group with GNAS1 mutations forming the molecular aetiology in approximately 50% of pseudohypoparathyroidism type Ia families. Such mutations can be reliably identified by single-stranded conformational polymorphism and this will help to supplement the clinical evaluation of some patients and their families, particularly as the disease may not be fully penetrant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
41
0
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(45 citation statements)
references
References 71 publications
3
41
0
1
Order By: Relevance
“…The crystal structure of Gα S revealed acidic residues in switch III that interact with basic ones in switch II and suggested that coupled dynamical changes in these two loop regions might be important for G-protein activation. Indeed, mutation of a conserved glutamate residue in switch III impairs receptor-mediated Gα S activation and the same residue is mutated in a patient with pseudohypoparathyroidism 30 . Mutation of the corresponding E232 residue in transducin decreases its downstream function, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of Gα S revealed acidic residues in switch III that interact with basic ones in switch II and suggested that coupled dynamical changes in these two loop regions might be important for G-protein activation. Indeed, mutation of a conserved glutamate residue in switch III impairs receptor-mediated Gα S activation and the same residue is mutated in a patient with pseudohypoparathyroidism 30 . Mutation of the corresponding E232 residue in transducin decreases its downstream function, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…But only the deletion in exon 7 can be considered a hot spot mutation [8][9][10] involving about 35% of all mutations described. Shapira et al [11] reported two patients with Albright's hereditary osteodystrophy, multiple hormone resistance, and deficient Gsa activity.…”
Section: Discussionmentioning
confidence: 99%
“…Heterozygous inactivating mutations of the GNAS1 gene, encoding for the G Sα protein, have been associated with parathyroid and thyroid hormone resistance in AHO patients [5, 12, 13]. In a series of 8 patients with AHO and PHP IA, GNAS1 mutations were found in half of the cases [14]. …”
Section: Discussionmentioning
confidence: 99%